2021
DOI: 10.3390/horticulturae7050115
|View full text |Cite
|
Sign up to set email alerts
|

Phenotyping Brown Rot Susceptibility in Stone Fruit: A Literature Review with Emphasis on Peach

Abstract: Plant disease phenotyping methodologies can vary considerably among testers and often suffer from shortcomings in their procedures and applications. This has been an important challenge in resistance breeding to brown rot, one of the most severe pre-and postharvest stone fruit diseases caused by Monilinia spp. Literature about methodologies for evaluating stone fruit susceptibility to brown rot is abundant but displays significant variations across the described approaches, limiting the ability to compare resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 104 publications
0
11
0
Order By: Relevance
“…5,[51][52][53][54][55][56] Post-harvest losses of 80-85% may occur under favourable conditions for brown rot development. 16 In Indiana, the brown rot of apples was discovered on the fruit of 'pristine' apples, causing 50% crop loss in 2015. 57 Other apple growers reported a significant loss of 5-20%.…”
Section: Economic Consequences and Recommended Phytosanitary Measuresmentioning
confidence: 99%
See 3 more Smart Citations
“…5,[51][52][53][54][55][56] Post-harvest losses of 80-85% may occur under favourable conditions for brown rot development. 16 In Indiana, the brown rot of apples was discovered on the fruit of 'pristine' apples, causing 50% crop loss in 2015. 57 Other apple growers reported a significant loss of 5-20%.…”
Section: Economic Consequences and Recommended Phytosanitary Measuresmentioning
confidence: 99%
“…58 Brown rot fungal infections can begin early in the growth season on blooms and/or young shoots. 16,59,60 While blossom blight outbreaks may not be severe enough to cause a serious decrease in fruit production, they still pose a risk. 59 At harvest, healthy fruit may be contaminated with spores, which then cause decay in storage and during marketing.…”
Section: Economic Consequences and Recommended Phytosanitary Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Disease and pest management techniques of horticultural crops have been undergoing major changes in recent years, with the push to create more sustainable production systems. While published studies on the methodologies for evaluating stone fruit susceptibility to brown rot are abundant, Mustafa et al [11] reported that significant variation in the various approaches have limited the ability to compare results from different studies. Thus, they reviewed the literature on phenotyping brown-rot susceptibility in stone fruit, focusing on peach (Prunus persica), and discussed ways to manage major factors affecting brown-rot phenotyping studies.…”
mentioning
confidence: 99%